Torsion of a growing shaft - Alexander V. Manzhirov; Mikhail N. Mikhin; Eugenii V. Murashkin (Vestnik Samarskogo Gosudarstvennogo Tehničeskogo Universiteta. Seriâ: Fiziko-Matematičeskie Nauki, 2017)
The torsion of a shaft by rigid disks is considered. The shaft has the form of circular cylinder. Two rigid disks are attached to its end faces. The process of continuous growth of such shaft under the influence of twisting torques applied to the disks is studied. Dual series equations which reflect the mathematical content of the problem at the different stages of the growing process are derived and solved. Results of the numerical analysis and singularities of the qualitative mechanical behaviour of the fundamental characteristics are discussed.